Performance, Meat Composition, Oxidative Stability and Fatty Acid Profiles of Broiler Chicken Using Moringa oleifera and Spirulina platensis as Feed Additives - Farhana Sharmin; Nathu Ram Sarker; Sadman Sakib Zihan; Md. Sazedul Karim Sarker (Contemporary Research and Perspectives in Biological Science Vol. 9, 2025)
The objectives of the present study were to evaluate the feeding effect of Moringa oleifera leaf meal and Spirulina platensis on their performance, oxidative stability and fatty acid profiles of broiler meat. A study was conducted to determine mainly the n-3 fatty acids enrichment and decreased oxidation of broiler meat using the plant M. oleifera and a blue green algae S. platensis. The advancements in poultry research have pooled knowledge of the biochemical and physiological mechanisms that increase the efficiency of feed utilization and desired carcass attributes through dietary manipulation. The effects of the dietary treatments were evaluated in terms of growth performance, carcass and meat yields, oxidative stability and fatty acids modulation. Two hundred and forty (240) one-day-old Cobb 500 broiler chicks were assigned to 5 dietary treatments for 5 weeks, with 4 replications having 12 chicks per replication. The diets of the treatments were formulated from the basal feed as follows: control (T1), including 2 different levels of M. oleifera leaf meal 1% (T2) and M. oleifera leaf meal 1.5%, (T3) and 2 different levels of S. platensis 1% (T4) and S. platensis 1.5% (T5). The birds were randomly distributed in each pen, and the data were analyzed using the SPSS statistical package. The final body weight (BW) gain was significantly higher in the T2 and T5 groups, and the feed conversion ratio improved in the T2 group (1.68). The results from the thiobarbituric acid-reactive substances values (TBARS) test provided evidence that the additives groups could improve the oxidative stability in broiler meat. These 2 substances, M. oleifera and S. platensis, may intercept and neutralize free radicals, preventing the oxidation process propagation. The lowest (p \(\) 0.05) TBARS of breast and thigh meat were obtained in T2 groups compared to T3-T5 group after the second week of preservation. Regarding the fatty acid profile of breast and thigh meat, the omega-3 fatty acid levels, such as those of linolenic and docosahexaenoic acid (DHA), were increased in the additive groups. The results of the present study elucidated that dietary inclusion of the 2 medicinal plants in the T2 and T5 groups could be promising functional ingredients to produce value-added broiler meat in terms of oxidative stability and omega-3 fatty acids enhancement. Furthermore, additives groups increased the \(ω\)3 fatty acid in breast and thigh meat. Therefore, M. oleifera leaf meal and S. platensis could be promising functional ingredients in broiler chicken meat production.